\[\boxed{\text{141\ (141).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\frac{|y + 7|}{y + 7} = 1;\ \ y \neq - 7\]
\[при\ y + 7 \geq :\]
\[|y + 7| = y + 7\]
\[\frac{y + 7}{y + 7} = 1\]
\[y + 7 > 0\]
\[y > - 7.\]
\[Ответ:x \in ( - 7;\ + \infty).\]
\[2)\ \frac{|6 - y|}{y - 6} = 1;\ \ \ y \neq 6\]
\[При\ 6 - y < 0:\]
\[|6 - y| = - (6 - y) = y - 6.\]
\[\frac{y - 6}{y - 6} = 1\]
\[6 - y < 0\]
\[y > 6.\]
\[Ответ:x \in (6; + \infty).\]
\[\boxed{\mathbf{141.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ (x + 3)^{4} - 3 \cdot (x + 3)^{2} - 4 =\]
\[= 0\]
\[\left\{ \begin{matrix} (x + 3)^{2} = t\ \ \ \ \ \ \\ t^{2} - 3t - 4 = 0 \\ \end{matrix} \right.\ \]
\[t_{1} + t_{2} = 3,\ \ t_{1} \cdot t_{2} = - 4,\ \ \]
\[t_{1} = 4,\ \ t_{2} = - 1\]
\[Ответ:\ x = - 1;\ x = - 5.\]
\[\left\{ \begin{matrix} (2x + 1)^{2} = t\ \ \ \ \\ t² - 10t + 9 = 0 \\ \end{matrix} \right.\ \]
\[t_{1} + t_{2} = 10,\ \ t_{1} \cdot t_{2} = 9,\ \ \]
\[t_{1} = 9,\ \ t_{2} = 1\]
\[Ответ:x = 1;\ x = - 1;x = 0;\ \]
\[x = - 2.\]
\[\left\{ \begin{matrix} (6x - 7)^{2} = t\ \ \\ t^{2} + 4t + 3 = 0 \\ \end{matrix} \right.\ \]
\[t_{1} + t_{2} = - 4,\ \ t_{1} \cdot t_{2} = 3,\ \ \]
\[t_{1} = - 3,\ \ t_{2} = - 1\]
\[Ответ:нет\ корней.\]
\[4)\ (x - 4)^{4} + 2 \cdot (x - 4)^{2} - 8 =\]
\[= 0\]
\[\left\{ \begin{matrix} (x - 4)^{2} = t\ \ \ \ \ \\ t^{2} + 2t - 8 = 0 \\ \end{matrix} \right.\ \]
\[t_{1} + t_{2} = - 2,\ \ t_{1} \cdot t_{2} = - 8,\ \ \]
\[t_{1} = - 4,\ \ t_{2} = 2\]
\[Ответ:x = 4 + \sqrt{2};\ \ \ x = 4 - \sqrt{2}.\]